ANALISIS PENDAPATAN PETERNAK ITIK PEDAGING BERDASARKAN SKALA USAHA YANG BERBEDA DI DESA SIPODECENG KECAMATAN BARANTI KABUPATEN SIDRAP - Resky Yudha Prawira; V. S. Lestari; Sitti Nurani Sirajuddin (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. The purpose of this study was to determine the operating revenue based scale broiler breeder of different businesses in the District Baranti, Sidrap. This study was conducted in November 2014 to February 2015. Located in the village of Sipodeceng, District Baranti, Sidrap. This research is descriptive quantitative research is a type of research that will describe the level of operating revenues of duck meat at different scale. Population broiler breeder ducks Sipodeceng Village, District Baranti,  Sidrap of 35 Breeders. The sampling technique was purposive with consideration that the farmers who  raise cattle broiler ducks during one period in 70 days conducted semi-intensive. The type of data in the form of quantitative data, the data source in the form of primary data and secondary data. Data collection techniques such as observation and interviews. Analysis of the data used to determine the operating revenues of duck meat by using statistical analysis deskrektif ie deskreptif. Based onthe research results it can be seen that the average income of farmers in the village of broiler ducks Sipodeceng District of Baranti Sidrap vary at each scale businesses owned, the largest revenue are on a scale of 1001-1500 in the amount of Rp. 23,901,389, - per period at a cost of rupiah per cow. Rp. 18 389.While the smallest on a scale of 100-300 is Rp. 1,460,875, - per period at a cost of rupiah per cow. Rp. 6,506. The difference in the income of farmers due to differences in the number of livestock owned broiler ducks. The larger the scale of business, the higher the income.